A pathway to greater meaning in life and well-being for senior executives beset by anti-meaning - Kruger, Juan-Mari; De Klerk, Jeremias Jesaja (Frontiers in Psychology, 2023)
Introduction: Although work is a significant source of meaning for most people, the role of senior executive generates different meaning and well-being complexities than those experienced or faced by general employees. This study explored how meaning and anti-meaning components affect senior executives’ experiences of meaning in life and well-being. The findings enabled devising a pathway to enhance senior executives’ net experiences of meaning in life and well-being. Methods: A cross-sectional, semi-structured interview study design was used to gather rich qualitative data. Eight participants from southern and eastern Africa, who had held the position of chief executive officer or managing director for at least five years, were interviewed. Results: The findings demonstrated that senior executives’ work roles provide a significant source of meaning. However, the roles are accompanied by unavoidable anti-meanings, which are likely to generate additional anti-meanings if not tempered sufficiently, thus reducing the net meaning experienced. Discussion: From the findings, a practical pathway was devised to assist top executives to deal with the bipolar relationship between meaning and anti-meaning. Consulting and counseling practitioners can utilize the pathway to guide, support, and counsel senior executives towards improved meaning, temper anti-meaning and improve well-being.